Dakwah Santun TGH. Akmaludin dalam Membangun Budaya Religius - muhammad deni azhari; akhmad ramidi (Institut Agama Islam (IAI) Nurul Hakim, 2023)
TGH Akmaludin's role is very decisive in cultivating religious culture in the Majlis Taklim Darul Huffaz, because the figure of the master teacher is seen as a figure who is 'pious, pious, noble and authoritative. By cultivating religious culture, religious cultures will grow in the Majlis Taklim Darul Huffaz in Parampuan Village, and with the authority of the leadership of the teacher, it will have a big influence on the development of religious culture. Therefore, researchers are interested in researching the role of TGH. Akmaludin in building religious culture. By examining the role of TGH leadership. Akmaludin in developing religious culture, this research aims to find out, (1) What is the role of TGH. Akmaludin in building religious culture in Parampuan Village, (2) What are Akmaludin's Hajj teacher programs in building religious culture in Parampuan Village? This research is a type of qualitative research with a phenomenological approach in studying religious culture in the Darul Huffaz Islamic boarding school. Data collection was carried out by, (1) observation, Majlis Taklim Darul Huffaz, (2) interviews with TGH. Akmaludin as the founder of the majlis taklim, management, community and congregation, (3) documentation of data related to the institution of the majlis taklim Darul Huffaz. The research results show: First, the role of Tuan Guru Akmaludin in the Darul Huffaz taklim assembly; Lecturer, role model, Koran teacher, leader and founder of Majlis Taklim Darul Huffaz. Second, the program offered by Tuan Guru Haji Akmaludin in building religious culture in Parampuan village is; daily (Diniyah), weekly (Majelis Taklim), and monthly (celebration of Islamic holidays) activities. Daily activities provide opportunities for the congregation to recite the Koran and understand Islamic teachings. Weekly activities focus more on discussions and group learning about the teachings of the Islamic religion. The monthly activity is recitation or studying the contents contained in the Al-Qur'an and Al-Hadith.